Domestic Air Traffic for Passengers on Saudi Arabian Airlines: Case Study of King Abdulaziz Airport in Jeddah - Alansari, Manal Saleh (Journal of natural sciences, life and applied sciences, 2021)
The study addresses the domestic passenger air traffic at King Abdulaziz Airport in Jeddah, which is one of the most important airports in Saudi Arabia and a portal to the Two Holy Mosques, serving the population of the region's governorates through the Saudi Arabian Airlines Company; one of the oldest airlines in the Arab world.The study aims to analyze the volume of internal passenger air traffic in the area of study; determining the directions of this movement by identifying the most momentum routes because it's a vital aspect to airport and airline management, as the traffic volume is considered to be one of the most important criteria that define airlines significance and their trends at the level of urban centers in different regions.To achieve the study's objectives, a descriptive and analytical approach was used to describe the studied phenomenon and its affecting factors. A quantitative approach was also used to tabulate and classify the study data. Figures, graphs, and cartographic style were used to present results and conclusions.The study concluded with presenting the most important results that have been reached- a variation in the volume of movement of arrivals and departures according to months and seasonality affecting the study area.There is also a variation in the number of internal passengers between different routes due to the difference in the functions of airport cities and their inhabitants’ number as well as the natural conditions and economic activities that characterize some cities, and the impact of other ways of transport on the volume of air transport and airports' competition in the same region, especially airports that are located in cities with a large population.As for the most moving routes in the study area, passenger traffic was concentrated in five air routes with a rate of (77.57%) of the total passenger traffic volume on all routes.
Keywords: air transport; air traffic; King Abdul Aziz Airport; Saudi Airlines passengers